Nilai Pendidikan Dalam Tari Dewa Ayu Di Desa Pemuteran, Kecamatan Gerokgak, Kabupaten Buleleng - Ni Wayan Karmini; I Wayan Diana (Jurnal Penelitian Agama Hindu, 2022)
This scientific work aims to discuss the procession of the dewa ayu dance and it’s value of Hindu religious education contained in this dance. This scientific work is the result of qualitative research whose data was collected through observation, documentation studies and in-depth interviews with Pemuteran village traditional leaders and observers of Balinese culture. Data analysis was carried out qualitatively descriptive by applying a number of eclectic theories, namely aesthetic theory, symbol theory and constructivism theory. The results of the study show that the indigenous people of Pemuteran Village are trying to preserve the Dewa Ayu Dance as an offering to Hyang Widi Wasa at the Panca Yadnya Ceremony. In general, the procession of the god ayu dance can be divided into three parts (1) canang sari and incense offerings by stakeholders; (2) ngurek, which is the stage of the dancers who are accompanied by stakeholders who experience a disturbances by stabbing themselves with a dagger they carry; (3) the dancers' awareness stage from distress to the normal situation. Pemangku took a keris from a dancer to be given a tirta and brought to its place (innards). Dewa Ayu dance has educational values, including: the value of togetherness education, the value of tattwa education, the value of moral education, ceremonial education, and the educational value of appreciation of art and culture. As part of efforts to preserve guardian dance (sacred), the tradition of Dewa Ayu dance performances in the life of Pemuteran Village community needs to be preserved.